PENERAPAN APLIKASI EDMODO: SALAH SATU EMBRIO MENINGKATKAN KOMPETENSI ABAD 21 PARA CALON DOSEN SEKOLAH DASAR - EKOWATI, DYAH WOROWORASTRI; Suwandayani, Beti Istanti; Soenaryo, Siti Fatimah (Universitas Negeri Semarang, 2019)
In the 21st century, it requires someone including prospective elementary school lecturers to master various competencies. Among the competencies referred to include 4C including Critical Thinking and Problem Solving (critical thinking and problem solving), Creativity (creativity), Communication Skills (ability to communicate), and Ability to Work Collaboratively (ability to work together). The mastery of 4C will then be discussed in depth in the application of edmodo applications in the Elementary School Lecturer Education Program (PGSD) University of Muhammadiyah Malang (UMM). The expected results can be one of the embryos that can improve the competency of prospective elementary school lecturers in the future.